Do Terrorism And Wars Have A Negative Effect On Hotel Industry Perceptions By Hotel Management Students? (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: This paper discusses the effect of terrorism and wars on the hotel industry  of hotel management students. Methods: The impacts of these negative situations were tested from  the data collected from 265 students of various courses at the institute using a questionnaire.  Results: It was found that majority (49.8%) of the students do not regret in joining the industry after  terror attacks like that of 26/11. Also majority (62.9%) agrees to recommend hotel management  profession to their friends and they are not regretful of joining the profession.
Keywords: Terrorism; War; Hotel Management; Perception